1996
DOI: 10.1016/s0304-3959(96)03179-x
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies predict disability in patients with primary fibromyalgia

Abstract: We administered the Coping Strategies Questionnaire (CSQ) to 80 patients with fibromyalgia (FM) to determine the relationship between coping strategies and functional disability. A principal components factor analysis revealed two dimensions of patients' CSQ responses: Coping Attempts and Catastrophizing. Coping Attempts consists of five scales: Reinterpreting Pain, Ignoring Pain Sensations, Diverting Attention, Coping Self-Statements and Increasing Activity Level. Catastrophizing is comprised solely of the CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0
6

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(125 citation statements)
references
References 28 publications
3
116
0
6
Order By: Relevance
“…We assessed thresholds for the perception of "moderate pressure" and for "faint pain" produced by the dolorimeter at 5 paired (left, right) tender points (TP) and 5 paired control points (CP) using a procedure that is standard in our laboratory (15,17,23,40,48,49). The TPs, which are a subset of those included in the ACR classification criteria for FM, include: 1) knee at the medial fat pad; 2) second rib at the second costochondral junction; 3) gluteal muscle at the upper quadrant of the buttocks; 4) trapezius muscle at the midpoint of the upper border; and 5) cervical region at the anterior aspect of the intertransverse spaces at (25x7.…”
Section: Cmz)mentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed thresholds for the perception of "moderate pressure" and for "faint pain" produced by the dolorimeter at 5 paired (left, right) tender points (TP) and 5 paired control points (CP) using a procedure that is standard in our laboratory (15,17,23,40,48,49). The TPs, which are a subset of those included in the ACR classification criteria for FM, include: 1) knee at the medial fat pad; 2) second rib at the second costochondral junction; 3) gluteal muscle at the upper quadrant of the buttocks; 4) trapezius muscle at the midpoint of the upper border; and 5) cervical region at the anterior aspect of the intertransverse spaces at (25x7.…”
Section: Cmz)mentioning
confidence: 99%
“…The dolorimeter was then withdrawn and the stimulus intensity that evoked the subject's response was recorded. After the moderate pressure threshold procedure was completed, the research assistant performed an identical procedure, previously described by our group (15,17,23,40,48,49), to assess pain threshold (i.e., initial perception of "faint pain" with dolorimeter stimulation) at each TP and 8.…”
Section: Cmz)mentioning
confidence: 99%
“…Catastrophizing is defined as a maladaptive response to pain and is characterized by an experience of heightened pain intensity and difficulty in disengaging from pain (6); it is an important predictor of pain severity, and of how people cope with pain (7)(8)(9), and appears to predict future disability better than do other variables (6). Some studies have indicated that pain catastrophizing predicts depression or even mediates the reduction in depression, the perception of pain and the behaviour in response to cognitive-behavioral or graded-exercise therapy (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that the catastrophic vision of pain is related not only to the pain the patients mention but also to other aspects that influence the course of the illness. Some studies show that patients with musculoskeletal pain with these ideas have a higher degree of disability, 78 higher use of health resources, 100 higher use of medication, 7,48 and worse recovery after knee arthroplasty surgery. 60 Many studies confirm a strong association between the ideas of pain catastrophization and the patient's disability in several conditions with chronic pain mainly in musculoskeletal pain.…”
Section: Catastrophizationmentioning
confidence: 99%